2018
DOI: 10.1021/acs.jafc.8b00094
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Multiresidue Analysis Method for 379 Pesticides in Human Serum Using Liquid Chromatography–Tandem Mass Spectrometry

Abstract: A screening method for simultaneous analysis of 379 pesticides in human serum was developed using liquid chromatography-tandem mass spectrometry (LC-MS/MS). Electrospray ionization with positive/negative switching mode of LC-MS/MS was adopted, and scheduled multiple reaction monitoring for each target compound was established. The limit of quantitation was 10 ng/mL for 94.5% of the total pesticides, and the correlation coefficients of calibration were ≥0.990 for 93.9% of the pesticides. For the sample preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 47 publications
1
25
1
1
Order By: Relevance
“…Additionally, Tables 2 and 3 presented the LOQs for the 34 multi-classes pesticides as well as under extraction of Group A and Group S. The results revealed that the LOQs of 26 and 31 pesticides in Groups A and S, respectively, was 1 µg/L. Moreover, the LOQs for our method (1-5 µg/L) were lower than those obtained using the method for multi-classes pesticides that proposed by Shin et al (10-250 µg/L) [42], and were similar to those obtained using the method for single-classes pesticide described by Yamamuro et al (0.5-10 µg/L) [25]. In our study, the recoveries and detection limits of the pesticides obtained when salt-ACN was used as the purification reagent were higher than those obtained when ACN alone.…”
Section: Extraction Of Multi-classes Pesticides From Serumcontrasting
confidence: 58%
“…Additionally, Tables 2 and 3 presented the LOQs for the 34 multi-classes pesticides as well as under extraction of Group A and Group S. The results revealed that the LOQs of 26 and 31 pesticides in Groups A and S, respectively, was 1 µg/L. Moreover, the LOQs for our method (1-5 µg/L) were lower than those obtained using the method for multi-classes pesticides that proposed by Shin et al (10-250 µg/L) [42], and were similar to those obtained using the method for single-classes pesticide described by Yamamuro et al (0.5-10 µg/L) [25]. In our study, the recoveries and detection limits of the pesticides obtained when salt-ACN was used as the purification reagent were higher than those obtained when ACN alone.…”
Section: Extraction Of Multi-classes Pesticides From Serumcontrasting
confidence: 58%
“…For this reason, sensitive and specific multi-residue techniques covering a wide spectrum of toxic or potentially toxic environmental pollutants, can substantially contribute to minimizing the costs and maximizing the chance of assessing the exposure of wildlife to most of the relevant chemicals. Thus, some other authors have developed multi-residue and multi-class methods for the determination of drugs (Qie et al, 2019), or of pesticides (Shin et al, 2018;Srivastava et al, 2017), or of POPs in blood (Vijayasarathy et al, 2019), even some using a very small amount of sample (Shin et al, 2018). However, to our knowledge, none has been developed for the simultaneous detection of contaminants for all of these groups together.…”
Section: Introductionmentioning
confidence: 99%
“…For imidazolinones (imazapic, imazaquin, and imazethapyr), their recoveries were superior to those in our previous study using the same preparation in serum samples (Figure 2). Because imidazolinones are zwitterions, ion suppression is required using acidic buffers to improve extraction efficiencies in serum [35]. Urine, however, is generally acidic, so imidazolinones were fully extracted without the help of buffer reagents.…”
Section: Resultsmentioning
confidence: 99%
“…The Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) method introduced by Anastassiades and coworkers is one of the most effective methodologies overcoming the limits or drawbacks of other preparations [29]. The original QuEChERS optimized for crop samples has been modified according to analytical situations [30,31,32,33] and extended for matrix materials such as biological samples [34,35,36].…”
Section: Introductionmentioning
confidence: 99%